2016
DOI: 10.1007/s12262-016-1486-x
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Time 18F-FDG PET/CT Imaging in Initial Locoregional Staging of Breast Carcinoma: Comparison with Conventional Imaging and Pathological Prognostic Factors

Abstract: The aims of this retrospective study were to consider the diagnostic role of dual-time 18 F-fluorodeoxyglucose positron emission tomography and computed tomography ( 18 F-FDG PET/CT) in detection of breast carcinoma and axillary lymph node (ALN) status and to evaluate the primary tumor 18 F-FDG uptake pattern. Preoperative staging was performed by 18 F-FDG PET/CT in 78 female patients with breast carcinoma. Conventional imaging results were evaluated by breast magnetic resonance imaging (MRI) of 79 lesions in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 24 publications
(59 reference statements)
2
7
0
4
Order By: Relevance
“…The literature search identified 369 articles ( Fig. 1) and 11 of these studies [32][33][34][35][36][37][38][39][40][41][42] were included in the meta-analysis. The details of the study characteristics and FP/FN/TP/TN are presented in Tables 1-3, respectively.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The literature search identified 369 articles ( Fig. 1) and 11 of these studies [32][33][34][35][36][37][38][39][40][41][42] were included in the meta-analysis. The details of the study characteristics and FP/FN/TP/TN are presented in Tables 1-3, respectively.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…The reference standards were SLNB and/or ALND (n = 7) and histopathology (no mention of this detail, n = 4). Most studies [33][34][35][36][37][38][39][40][41] enrolled patients with confirmed invasive ductal carcinoma (IDC), invasive lobular carcinoma (ILC), or other specific types (n = 9). One study 42 included breast cancer subtypes with low FDG avidity (mucinous carcinoma [MC], tubular carcinoma [TC], and ILC) and another study 32 did not mention the histopathological type.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of cases are more common IDC in nearly all of the researches. In 6 studies investigating the contribution of late imaging with FDG-PET in breast cancer, the first bibliography of 2/56, 3/66, 13/86, 2/53, 8/48 and 2/38, respectively, was included in the studies and the rate was only 9% (30/347) (18)(19)(20)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that late imaging contributes to the diagnosis in malignancies, where the imaging quality will be optimal as much as the radiopharmaceutical half-life allows (12). There are many studies reporting that late image in FDG-PET in breast cancer significantly increases sensitivity and specificity (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). However, these studies mostly consist of IDC patients.…”
Section: Introductionmentioning
confidence: 99%